2017
DOI: 10.1136/bjsports-2017-098375
|View full text |Cite
|
Sign up to set email alerts
|

Poor overall quality of clinical practice guidelines for musculoskeletal pain: a systematic review

Abstract: Objectives Undertake a systematic critical appraisal of contemporary clinical practice guidelines (CPGs) for common musculoskeletal (MSK) pain conditions: spinal (lumbar, thoracic and cervical), hip/knee (including osteoarthritis) and shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 63 publications
5
66
0
4
Order By: Relevance
“…In the remaining 4 domains, overall scores <40% were obtained. In detail, domain 2 “Stakeholder involvement” obtained an average score of 38.43%, mainly due to the lack of information about target population views and preferences (domain 2), as also addressed by Lin and colleagues regarding the evaluation of guidelines for musculoskeletal pain . The noninvolvement of relevant professional figures other than radiologists in guideline's draft except for ACR guideline (in which neurologists, surgeons, and nuclear medicine specialists were also involved) could also explain this finding along with the highest variability (SD 20.62%) found among guidelines’ scores in this domain.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the remaining 4 domains, overall scores <40% were obtained. In detail, domain 2 “Stakeholder involvement” obtained an average score of 38.43%, mainly due to the lack of information about target population views and preferences (domain 2), as also addressed by Lin and colleagues regarding the evaluation of guidelines for musculoskeletal pain . The noninvolvement of relevant professional figures other than radiologists in guideline's draft except for ACR guideline (in which neurologists, surgeons, and nuclear medicine specialists were also involved) could also explain this finding along with the highest variability (SD 20.62%) found among guidelines’ scores in this domain.…”
Section: Discussionmentioning
confidence: 92%
“…In detail, domain 2 "Stakeholder involvement" obtained an average score of 38.43%, mainly due to the lack of information about target population views and preferences (domain 2), as also addressed by Lin and colleagues regarding the evaluation of guidelines for musculoskeletal pain. 25 The noninvolvement of relevant professional figures other than radiologists in guideline's draft except for ACR guideline (in which neurologists, surgeons, and nuclear medicine specialists were also involved) could also explain this finding along with the highest variability (SD 20.62%) found among guidelines' scores in this domain. Domain 3, "Rigor of development," scored an average percentage score of 33.85% since methods for searching or evaluating evidences were not always specified and no guideline authors' team applied the Delphi or Glaser technique to achieve a mutual agreement among experts.…”
Section: Discussionmentioning
confidence: 99%
“…Many systematic reviews have reported on the low quality of evidence concerning the relationship between musculoskeletal disease symptoms and physical activity level. Unfortunately, most studies have focused on generalized pain disorders including fibromyalgia and localized disorders of other body parts including the lower back, neck and shoulders . No study has considered the relationship between general physical activity level and TMD symptoms before, and this is the first attempt to define such an association.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the quality of general health information given in the AHG was found to be a complex task because there is little evidence available for the recommendations given. For example, it has recently been shown that clinical guidelines for musculo‐skeletal pain conditions in the general population are of inferior quality 39 . Nonetheless, in a society with virtually infinite access to information, it is of utmost importance that a sports organization take responsibility for the information conveyed to its members.…”
Section: Discussionmentioning
confidence: 99%